Big data analytics for connected vehicles and smart cities - McQueen, Bob (Artech House power engineering series., 2017)
This practical new book presents the application of "big data" analytics to connected vehicles, smart cities, and transportation systems. This book enables transportation professionals to understand how data analytics can and will expand the design and engineering of connected vehicles and smart cities. Readers find extensive case studies and examples that provide a strong framework focusing on practical application of data sciences and analytic tools for actual projects in the field.n nBoth federal and private sector investments have a strong interest in the connected vehicle and this book discusses the impact this has on transportation. This book defines urban analytics and modeling, incentives and governance, mobility networks, energy networks, and other attributes and elements that craft a smart city. Readers learn how smart cities impact the application of advanced technologies in urban areas. This book explains how recently passed transportation legislation for the US has a specific emphasis on the use of data for performance management.